2015
DOI: 10.1111/inr.12219
|View full text |Cite
|
Sign up to set email alerts
|

Weight management care practices of English and Chinese nurses

Abstract: Skill development of pre-registration and qualified nurses is indicated as well as the development of the nurse role to include weight management care of obese patients. Evidence-based guidelines should be readily accessible to support the nurse role in weight-related care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…Similarly, school nurses found that broaching the subject of obesity with parents was challenging and that they faced backlash from parents as a consequence. This difficult conversation has been identified in other populations as a barrier to referrals into weight management services [ 26 29 ].…”
Section: Main Textmentioning
confidence: 99%
“…Similarly, school nurses found that broaching the subject of obesity with parents was challenging and that they faced backlash from parents as a consequence. This difficult conversation has been identified in other populations as a barrier to referrals into weight management services [ 26 29 ].…”
Section: Main Textmentioning
confidence: 99%